1994
DOI: 10.1007/bf00351485
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the cerato-ulmin toxin gene of the Dutch elm disease pathogen, Ophiostoma ulmi

Abstract: The hydrophobic protein cerato-ulmin (CU), produced by Ophiostoma ulmi, has been implicated in the pathogenicity of this fungus on elm. Primers were designed based on the nucleotide sequence deduced from the published CU amino-acid sequence, and a DNA fragment of the cu gene was amplified using the polymerase chain reaction. The amplified cu fragment was used as a hybridization probe to identify and isolate the cu gene from a genomic DNA library of an aggressive isolate of O. ulmi ( = O. novo-ulmi). The cu cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…The high similarity in primary structure and conservation of intron positions suggest that the hJb2 gene has a common ancestor with the previously characterized 7: reesei hydrophobin hjbl (Nakari-Setala et al, 1996) and with the two other class I1 hydrophobins characterized, the cryparin of Cryponectria parnsitica (Zhang et al, 1994) and cerato-ulmin of Ophiostoma ulmi (Bowden et al, 1994; Fig. 1). hjb2 was isolated using the hfll gene as a probe, which indicates that heterologous hybridization might be a generally useful technique for isolation of hydrophobin genes.…”
Section: Discussionmentioning
confidence: 69%
“…The high similarity in primary structure and conservation of intron positions suggest that the hJb2 gene has a common ancestor with the previously characterized 7: reesei hydrophobin hjbl (Nakari-Setala et al, 1996) and with the two other class I1 hydrophobins characterized, the cryparin of Cryponectria parnsitica (Zhang et al, 1994) and cerato-ulmin of Ophiostoma ulmi (Bowden et al, 1994; Fig. 1). hjb2 was isolated using the hfll gene as a probe, which indicates that heterologous hybridization might be a generally useful technique for isolation of hydrophobin genes.…”
Section: Discussionmentioning
confidence: 69%
“…Insertional mutagenesis, analysis of genetic crosses and inspection of Ophiostoma spp. genomes revealed evidence about the function of some genes such as Cu (encoding the toxin cerato-ulmin, Bowden et al 1994Bowden et al , 1996, Pat1 (encoding a pathogenicity factor, Et-Touil et al 1999), Epg1 (encoding the enzyme endopolygalacturonase, Temple et al 2009) and the presence of DNA transposons (Bouvet et al 2007). More recently, extensive transcriptomic studies using an advanced molecular tool (RNAseq) have identified differential gene expression in the distinct phases of O. novo-ulmi from yeast to hyphae and mycelium Nigg and Bernier 2016).…”
Section: Molecular Advances To Understand the Genetic Clues Behind Elmentioning
confidence: 99%
“…It has been found that CU is a hydrophobin (Stringer & Timberlake, 1993 ;Bowden et al, 1994 ;Templeton et al, 1994) that may be involved in recognition phenomena or in functions other than the toxic activity specific towards elm. The detection of CU on the cell wall surface of O. piceae, a saprotroph on elm, confirms this hypothesis.…”
Section: Discussionmentioning
confidence: 99%